The problem of revaluation - McElligott, C. C. (Statistical and Social Inquiry Society of Ireland, 1955)
My first duty is to thank the President and Council of the Society for the honour they have conferred on me in inviting me to read a paper on this important and controversial subject, ?The Problem of Revaluation.? You may have revaluation for many different purposes but tonight our sole concern is with rateable valuations, and the views I express are purely personal. Our subject falls naturally under two main heads?firstly, the origin, extent and nature of our existing valuations, and secondly, the changes that would be wrought in the existing system by a revaluation.
Read before the Society, 28 January 1955
Keywords: Currency revaluation; Exchange rate regimes; Irish exchange rate regimes; Sterling peg; 314.15